Analisis Administrasi Dalam Bidang Peserta Didik Di SDIT-Al-Izhar School - Fitria Nurkarimah; Nyai Ai Nurjanah; Putri Zahara; Adinda Dwi Putri; Novrian Ramadhan; Sakban Sakban (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Student administration is important for continuous learning in schools. Activities that are important in managing first-time student registration. This research explains about students at school. The aim of this research is to describe student administration in the school environment using SWOT analysis. Based on the SWOT analysis of student administration at the school, the appropriate method for this research is to use qualitative research with a descriptive approach. Data collection techniques include: observation, interviews, notes, and documentation. We can conclude from the results of this main analysis that there is still a need to develop strategies and improve the quality of schools to increase community interest in registering their children.